2015
DOI: 10.1371/journal.pgen.1005531
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Regulatory Program for Meiotic Prophase in the Fetal Ovary

Abstract: The chromosomal program of meiotic prophase, comprising events such as laying down of meiotic cohesins, synapsis between homologs, and homologous recombination, must be preceded and enabled by the regulated induction of meiotic prophase genes. This gene regulatory program is poorly understood, particularly in organisms with a segregated germline. We characterized the gene regulatory program of meiotic prophase as it occurs in the mouse fetal ovary. By profiling gene expression in the mouse fetal ovary in mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(159 citation statements)
references
References 57 publications
7
152
0
Order By: Relevance
“…Dotted circles represent samples under the same culture periods. Arrows highlight the differences between the WT and SK cells. Scatter‐plot comparison of gene expression between the WT and SK1 c9 RAB2 cells and the expression of genes reported to be independent (blue), partially dependent (pink), and dependent (red) on Stra8 (Soh et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dotted circles represent samples under the same culture periods. Arrows highlight the differences between the WT and SK cells. Scatter‐plot comparison of gene expression between the WT and SK1 c9 RAB2 cells and the expression of genes reported to be independent (blue), partially dependent (pink), and dependent (red) on Stra8 (Soh et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…IF analyses revealed that PGCLCs cultured with RA and BMP2 began to express STRA8, a key meiosis inducer (Baltus et al, 2006;Anderson et al, 2008;Dokshin et al, 2013;Soh et al, 2015), as early as c5 [~40.7%/SC (+) cells], and at c7 the vast majority (~91.7%) of SC (+) cells exhibited STRA8 expression, and some of them (~27.1%) were SCP3 (+) ( Fig 2B and C). Remarkably, at c9, more than 90% of SC (+) cells expressed SCP3 with synaptonemal complex-like structure formation, and STRA8 began to wane (Fig 2B and C).…”
Section: Bmp and Ra Commit Pgclcs To The Female Fatementioning
confidence: 99%
See 1 more Smart Citation
“…Soh et al have shown that Stra8 is involved in its own permanent downregulation after induction of meiosis in order to make sure that meiosis is commenced just once in the germ cells (Soh et al, 2015). Soh et al have shown that Stra8 is involved in its own permanent downregulation after induction of meiosis in order to make sure that meiosis is commenced just once in the germ cells (Soh et al, 2015).…”
Section: Meiosis Induction In Fetal Ovarymentioning
confidence: 99%
“…Chromosomal events comprising meiotic cohesin aggregation, synapsis formation, and recombination of homologous chromosomes constitute a chromosomal program.Soh et al have proposed that Stra8-dependent pathways regulate all of chromosomal program while the Stra8-independent pathways bring about stockpiling of specific structural components before the chromosomal program commences(Soh et al, 2015). have shown that under the regulation of RA, CYP51 translocates to the nucleus in the fetal ovarian germ cells thereby promoting meiosis.…”
mentioning
confidence: 99%